FT Pelatihan Pembuatan Evaluasi Pembelajaran dengan Menggunakan Google Formulir bagi Guru SDN 96/IV Kota Jambi - Sinaga, Rudolf; Afriany, Renny; Samsinar, Samsinar (Universitas Nusantara PGRI Kediri, 2024)
SD Negeri 96/IV is at Jalan Sunan Bonang RT. 32 Kel. Simpang III Sipin Kec. Kota Baru Jambi City. In the implementation of learning evaluation, teachers at this school apart from using the paper-based system, have also tried to use other media, such as Quiziz, and Google Forms. But in practice, it is still not used optimally, because the teachers have not gained good knowledge of the features and capabilities of each of these applications. Making learning evaluations is an important part of an effective learning process. Therefore, in the digital era, one of the most suitable media to use is Google Forms, because Google Forms can be used as a tool that can improve the quality and effectiveness in making learning evaluations or exam questions with several question models such as multiple choice, essay, and can add images and videos to the questions. Google Forms will also make it easier for teachers to collect and analyze exam data. Community service at this school was carried out in March 2023. Activities are carried out using presentation, training, and evaluation methods. The conclusions obtained through this community service activity are: 1. Improve teachers' understanding at SDN 96/IV about the features and capabilities of Google Forms, 2. Improve teachers' knowledge at SDN 96/IV in making learning evaluations using Google Forms.